Promosi Sekolah Berkelanjutan untuk Meningkatkan Penerimaan Murid Baru: Pengabdian Masyarakat di SD Al Muslim Bekasi - Isep Djuanda; Sri Andriyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The increasing competition among educational institutions requires schools to implement effective and sustainable promotion strategies to maintain public trust. This community engagement program aimed to strengthen the school’s image and increase new student enrollment through the implementation of a participatory school promotion campaign. The method used was Participatory Action Research (PAR), involving teachers, students, parents, alumni, and the surrounding community. The stages of the program included problem identification, planning, implementation, and evaluation. Promotional activities were carried out through social media campaigns, open house events, alumni testimonials, and partnerships with external institutions. The results showed a 20% increase in new student enrollment compared to the previous year, as well as greater.